2014
DOI: 10.2478/ceer-2014-0009
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Accumulation in Leaves of <i>Hydrocharis Morsus-Ranae L.</i> and Biomonitoring Applications

Abstract: In present study the concentrations of Hg, Mn, Zn, Fe and Cu in water, bottom sediments and leaves of Hydrocharis morsus-ranae from 11 oxbow lakes of the Odra River were determined by atomic absorption spectrometry. Trace metal concentration in water and bottom sediments were below the geochemical background, indicating no anthropogenic impact in the studied area. On average, the concentrations of metals in leaves of H. morsus ranae exceeded natural thresholds. A high bioaccumulation factors for metals were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…At the same time, the average concentrations of Zn, Mn, and Fe exceeded physiological values and corresponded to the level of toxicity (Polechońska, Dambiec, 2014).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…At the same time, the average concentrations of Zn, Mn, and Fe exceeded physiological values and corresponded to the level of toxicity (Polechońska, Dambiec, 2014).…”
mentioning
confidence: 77%
“…The high ability of H. morsus-ranae to accumulate such metals as Mn, Fe, Co, Ni, Zn, and Cu has already been noted (Brekhovskikh et al, 2009;Polechońska, Samecka-Cymerman, 2016). Polechońska and Dambiec (2014) reported that the contents of Mn, Fe, and Cu in the leaves of H. morsus-ranae exceeded the average levels observed for other floating macrophytes, even in cases of low metal content in water bodies.…”
mentioning
confidence: 92%
“…The studies conducted so far in natural aquatic ecosystems [GAŁCZYŃSKA, BEDNARZ 2012;POLECHOŃSKA, DAMBIEC 2014;POLE-CHOŃSKA et al 2017;POLECHOŃSKA, SAMECKA-CYMERMAN 2015;SKWIERAWSKI, SKWIERAWSKA 2013] show the possibility of occurrence of H. morsus-ranae in waters contaminated with metals, including heavy metals. The results confirming the accumulation of substantial amounts of metals in the plant's tissues as well as high efficiency of such accumulation in defined environmental conditions, support including H. morsus-ranae to a group of bioindicators of waters contaminated with metals [GAŁCZYŃSKA 2012;POLECHOŃSKA, DAMBIEC 2014;POLECHOŃSKA et al 2017;POLECHOŃSKA, SAMECKA-CYMERMAN 2015]. Chlorophyll content is one of the parameters which may indicate the viability of a bioindicator when conducting studies.…”
Section: Introductionmentioning
confidence: 99%